Mekanisme Penyimpanan Dan Pemusnahan Benda Sitaan Narkotika Yang Telah Mendapatkan Kekuatan Hukum Yang Tetap (Incraht) - Sigit Muhaimin; Derry Angling Kesuma; Windi Arista (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
Narcotics are substances or drugs originating from plants or non-plants, whether synthetic or semi-synthetic, which can cause a decrease or change in consciousness, loss of taste, reduce or eliminate pain, and can cause dependence, which are divided into groups as mentioned in attachment to Law Number 35 of 2009 concerning Narcotics. The destruction of evidence in narcotics cases is regulated in Law Number 35 of 2009 concerning Narcotics and Regulation of the Head of BNN Number 7 of 2010 concerning Technical Guidelines for Safe Handling of Confiscated Narcotics Items.